1987
DOI: 10.2337/diacare.10.5.594
|View full text |Cite
|
Sign up to set email alerts
|

Macrosomia in Pregnancy Complicated by Insulin-Dependent Diabetes Mellitus

Abstract: We assessed the factors influencing the birth weight of infants born to 83 women with insulin-dependent diabetes mellitus (IDDM) over a 5-yr period. Maternal glycosylated hemoglobin (HbA1) concentrations at delivery correlated with the percentile birth-weight ratios (r = .43, P less than .001) and indicated that approximately 18% of variance in the birth weight could be ascribed to glycemic control in the third trimester. Fetal macrosomia occurred in 22 (27%) pregnancies. When 20 of these pregnancies were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…Third trimester HbA 1c was an independent risk indicator for macrosomia, which is in agreement with other studies [4,5]. A third trimester HbA 1c greater than 6.5% was associated with a twofold to threefold increase in macrosomia.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Third trimester HbA 1c was an independent risk indicator for macrosomia, which is in agreement with other studies [4,5]. A third trimester HbA 1c greater than 6.5% was associated with a twofold to threefold increase in macrosomia.…”
Section: Discussionsupporting
confidence: 92%
“…[Diabetologia (2002) rosomia is related to an increased risk for "unexplained" death in utero and shoulder dystocia during labour, the latter being related to asphyxia, clavicle fracture and/or Erbs palsy [1,2,3]. During the neonatal period macrosomic infants are at increased risk for hypoglycaemia, infant respiratory distress syndrome (IRDS), hyperbilirubinaemia and hypertrophic cardiomyopathy [4,5,6]. A number of long-term population studies have shown that macrosomic newborns of women with diabetes have a higher risk to develop obesity and Type II (non-insulin-dependent) diabetes mellitus at a young age [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the concept of maternal hyperglycaemia-fetal hyperinsulinism, one would also anticipate a parallel reduction in the incidence of macrosomia. This has not been the case; instead, the incidence of fetal macrosomia is unexpectedly high and the rate is increasing [3][4][5][6][7][8][9][10][11] . Thus, despite intensive treatment aiming at near-normoglycaemia, rates of macrosomia 6-10 times higher than normal have been recorded.…”
mentioning
confidence: 99%